PENGARUH SOSIALISASI UNDANG-UNDANG PERLINDUNGAN KONSUMEN TERHADAP KESADARAN BERKONSUMSI ANGGOTA WANITA CABANG TAMANSISWA DI YOGYAKARTA - Rina Setyaningsih (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2015)
The purpose of this study was to determine (1) the portrayal of the socialization of the consumer protection law (2) the portrayal of consumers’ awareness, and (3) the effect of the socialization of the consumer protection law on the consumption awareness among members of Tamansiswa Women Branch, in the city of Yogyakarta. The proposed hypothesis is: There is a positive and significant effect of the socialization of the consumer protection law to the awareness among members of the Tamansiswa Women Branch in the city of Yogyakarta. This research belongs to the study of ex post facto. The study population was all members of the Tamansiswa Women Branch in Yogyakarta, numbering 245 respondents. The sampling used a proportional random sampling technique, that is the sample drawn at random was 50%, numbering 123 plus 10% of the sample for the missing data and non-responses numbering 14 to make the total of 137. The data collection method used a questionnaire and documentation. The research instrument was a questionnaire and its measurement using a modified Likert scale. The instrument was tested to 30 Tamansiswa Women outside the sample but still within the population. To determine the validity of the instrument the product moment correlation analysis was used by correlating the score of each item with the total score, while the reliability test using Cronbach’s Alpha formula. The data analysis used descriptive analysis techniques and hypothesis testing used the Product Moment Correlation analysis formula, preceded by the test requirement analysis, namely the normality and linearity tests. The research results showed that the variable of consumer socialization of the protection law belonged to the high category with the relative frequency of 43.84% and the awareness to consume a high category with a relative frequency of 37.69%. Based on the analysis using the Product Moment there is a positive and significant relationship between the socialization knowledge of consumer law and the consumption awareness, with the coefficient value of rxy 0,741> 0,172 at the significance level of 5%. This result is also supported by the determinant coefficient value (R ²) of 0.63, meaning that the level of effect between the socialization of consumer protection laws with the awareness to consume is 63%, while the remaining 37% is affected by other factors not discussed in this study.